2014
DOI: 10.12681/ppej.62
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Administering a Needs Analysis Survey to Primary School Learners about EFL learning: a Case Study

Abstract: Summary. Needs analysis is a distinct and necessary phase in planning educational programs and curriculum development. It is used to collect information about learners' needs, focusing on the study of learners' perceived and present needs, as well as their potential and unrecognized needs. The purpose of this study was to develop, design and administer a needs analysis survey to a group of primary school learners in order to investigate their attitudes towards EFL learning, their actual foreign language needs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 34 publications
(35 reference statements)
0
20
0
4
Order By: Relevance
“…The need analysis can help them to clarify and validate the learners' true needs, as Akyel & Ozek (2010) have argued. By understanding the results of need analysis, they are able to translate the learners' needs into linguistics and pedagogical terms in order to teach an effective course (Tzotzou, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need analysis can help them to clarify and validate the learners' true needs, as Akyel & Ozek (2010) have argued. By understanding the results of need analysis, they are able to translate the learners' needs into linguistics and pedagogical terms in order to teach an effective course (Tzotzou, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of needs analysis have been undertaken over the last three decades (Widodo, 2016) and a number of contemporary researches on this issue have mushroomed in many different countries, such as Greece (Chostelidou, 2010;Tzotzou, 2014), Iran (Aliakbari & Boghayeri, 2014;Atai & Shoja, 2011;Boroujeni & Fard, 2013;Eslami, 2010;Mohammadi & Mousavi, 2013;Moiinvaziri, 2014), Spain (Benavent & Sánchez-Reyes, 2015;Peters & Fernández, 2013), Sudan (Elsaid Mohammed & Nur, 2018), USA (Bosher & Smalkoski, 2002;Serafini, Lake, & Long, 2015), Japan (Cowling, 2007), China (Guiyu & Yang, 2016;Li, 2014;Wu, 2012;Zhu & Liu, 2014), Turkey (Akyel & Ozek, 2010;Kayiran & Bağçeci, 2018), KSA (Abdalla & Mohammed, 2016;Al-Qahtani, 2015;Alsamadani, 2017;Fadel & Rajab, 2017), Taiwan (Chen, Chang, & Chang, 2016;Lu, 2018), Thailand (Bosuwon & Woodrow, 2009;Prachanant, 2012), and Indonesia (Nimasari, 2018;Poedjiastutie & Oliver, 2017;Sabarun, 2019;Salam, 2017). Those literatures reflect the centrality and the inevitable role of need analysis in establishing an ESP course.…”
Section: Introductionmentioning
confidence: 99%
“…All teachers believe that it is important for their students to follow a course that has been designed according to their needs. As teachers mentioned, becoming aware of their students' needs can enhance students' motivation in class, as has already been reported in the literature (Tzotzou, 2014). Drawing attention to students' motivation implies a focus on their subjective needs, which is also highlighted by teachers.…”
Section: Discussionmentioning
confidence: 76%
“…In addition to the aforementioned types of needs, a NA procedure may focus on the considerations of the learners' language needs as a product or as a process. In this regard, Tzotzou (2014) suggests that NA involves objective needs and subjective needs, such as motivation and personal learning preferences. It should be observed that a subjective process-oriented perspective to NA is employed in the present study.…”
Section: Na: Theoretical Backgroundmentioning
confidence: 99%